GÊNERO, MULHERES E VERDADES JURÍDICAS NA COMARCA DE GUARAPUAVA-PR: (DÉCADA DE 1960) - CALDAS, VALÉRIA LEITE (2022)
The present research aims to analyze discursive statements about women victims of homicide by husbands, lovers, or acquaintances. Having as a space-time cut the District of Guarapuava in the 1960s. For this, we selected as sources three criminal cases and a police inquiry that are available in the AHM-CEDOC/G of UNICENTRO. In a qualitative approach, we used the Gender category to problematize the narratives about the murdered women and the defendants, allied to the Foucauldian understanding of Discourse. We also analyzed data referring to crimes and criminality in the District of Guarapuava and focused more carefully on the legal documents of cases in which women were murdered: the places/scenarios; generation; schooling; finally, how defendants and victims were described from the perspective of the judicial apparatus, witnesses and the defendants themselves, and how these narratives structure the outcomes of cases, the construction of sentences, the construction of outcomes of legal truths existing in criminal proceedings.